PENDIDIKAN NILAI SEBAGAI KOMPONEN INTEGRAL PENDIDIKAN UNTUK MENGHADAPI TANTANGAN ABAD XXI - PRIYOYUWONO, PETRUS (Universitas Negeri Yogyakarta, 2003)
The purpose of education is in fact to improve the quality of one's life. Without ruling out the benefit and economic purposes, education has produced present generation with the most in number of experts and trained workers who makes fast progress within the science, knowledge and technology. even though in its process, mankind's interest, cultural and ethical values are often ignored The components of value education need to be put in the curriculum at different school level using various strategies. The value education is a task and responsibility of schools as well as parents.